2008
DOI: 10.1002/art.23325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postmenopausal hormone therapy on rheumatoid arthritis: The women's health initiative randomized controlled trials

Abstract: Objective. To study the effects of postmenopausal hormone therapy (PHT) on the incidence and severity of rheumatoid arthritis (RA). Methods. The Women's Health Initiative randomized controlled trials evaluated the effects of unopposed estrogen (E-alone) and estrogen plus progestin (E؉P) compared with placebo on a diverse set of health outcomes over 7.1 and 5.6 years, respectively. RA cases were identified using historical and medication data. The hazard of developing RA was estimated using Cox proportional haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 35 publications
0
61
1
3
Order By: Relevance
“…Consistent with this possibility, the incidence of rheumatoid arthritis among women rises in the immediate postmenopausal years, and premature menopause is associated with higher disease risk. Postmenopausal hormone supplementation appears to afford minimal, if any, protection perhaps because IgG glycosylation represents only one of many factors associated with disease risk (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, the incidence of rheumatoid arthritis among women rises in the immediate postmenopausal years, and premature menopause is associated with higher disease risk. Postmenopausal hormone supplementation appears to afford minimal, if any, protection perhaps because IgG glycosylation represents only one of many factors associated with disease risk (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown oral contraceptive pill use to be associated with a lower RA risk, this observation was refuted in a more recent well-designed, prospective investigation [32]. Recent reports similarly found no associations of hormone replacement therapy with RA onset [33,34]. Results of investigations of potential endogenous hormonal factors in RA have also yielded inconsistent results.…”
Section: Reproductive Factorsmentioning
confidence: 90%
“…Accumulating evidences showed that sex hormones are implicated in the immune response, and antibody production to antigenic stimulation is greater in women than in men [42,43] . Although conflicting results were reported in the effects of hormone therapy on RA, some clinical trial showed that hormone-containing estradiol has a beneficial effect on disease activity, inflammation and progression of radiological joint destruction [44,45] . Consistent with the findings of previous reports on EORA patients [9,34] , we showed a higher proportion of men and a lower frequency of RF positivity in EORA patients when compared with YORA patients.…”
Section: Discussionmentioning
confidence: 99%